Funeral Hymns of Lithuanians and Vilnius Region Poles’: General Features and Trends of the Repertoire - Žičkienė, Aušra; Syrnicka, Kristina (Vilnius University Open Series, 2020)
The article discusses the key features and trends of the repertoire of Catholic funeral hymns, functioning in Lithuania in both Polish and Lithuanian; at the same time attempts are made to grasp the possible causes of mutual interactions and influences. In combining literary and ethnological approaches, field research data, historical sources, printed and manuscript hymns are analysed and interpreted, related scientific literature is examined. The conclusion is reached that the similarity and commonalities of the Lithuanian and Vilnius Region Poles’ folk piety funeral repertoire were, and still are, a result of similar cultural conditions. The basis of the old repertoire is primarily determined by trends, influences, and themes coming from Poland, while the areas of the modern repertoire’s influence are much broader: both general international trends and a broad mutual influence can be noted.In Lithuania’s villages and cities it is still common practice to invite a group of hymn-singers to a funeral wake and burial ceremony. Singing of funeral hymns is an old tradition, likely coming from the 17th c., from Poland, slowly covering also the territory of modern-day Lithuania and gradually settling down, gaining distinct regional features. However, we do not have any accounts as to whether a folk piety funeral repertoire existed in Lithuanian – it likely formed later.The texts of funeral songs can be divided into several groups according to their origin and function: some are adapted from church liturgies and are traditional church hymns, while others were created at different times by either anonymous local authors or well-known songwriters. Some hymns, for a long time, functioned as part of the liturgy of death and funerals, they established themselves in the practice of folk piety, while others became part of the funeral repertoire when they came into it from various thematically-fitting church calendar holidays or they were created by known or (more often) anonymous songwriters, then spreading among the people.The similarities of the repertoire of Lithuanian and Polish funeral songs are first of all a result of close cultural conditions. The texts of the oldest repertoire of funeral hymns were usually translated from Polish to Lithuanian, with the former taking root in the practices of folk piety much earlier. The melodies of hymns also mostly came from Poland; many are of liturgical origin, although over the centuries they grew into the local musical environment and gained a distinctive tone.The trends of the formation of the new hymns (from the beginning of 20th c. until now), on the one hand, are a continuation of the previous ones; however, on the other hand, local (Lithuanian) features, resulting from the faster and wider spread of information, become clearer, as well as various international influences. A certain group of hymns exists only in Lithuania, we can clearly see the influence of the Lithuanian environment on the poetry and melodics of Polish-language funeral hymns. This repertoire spreads only through writing down by hand the texts, while melodies are learned by ear; they are not published in any hymnals approved by the Church.
Keywords: funeral songs; folk piety; Lithuanians; Poles; Vilnius region; song book